Conformational analysis of bovine serum albumin adsorbed on halloysite nanotubes and kaolinite: a Fourier transform infrared spectroscopy study. Issue 76 (1st August 2016) - Della Porta, Valentina; Bramanti, Emilia; Campanella, Beatrice; Tiné, Maria Rosaria; Duce, Celia
Abstract : Clay minerals are widely used in pharmaceutical formulations, therefore studying how they interaction with proteins is important because they can alter their biological functions. Abstract : Clay minerals are widely used in pharmaceutical formulations, therefore studying how they interaction with proteins is important because they can alter their biological functions. The interactions of proteins with nanostructured clays and, in general, with nanomaterials should also be studied because nanoparticles are known to interfere with protein amyloid formation, which is implicated in severe neurodegenerative diseases. Kaolinite and halloysite belong to the kaolinite group of minerals with the nominal formula Al2 Si2 O5 (OH)4 per half unit cell, however they have important structural layer stacking differences. We studied the surface interactions between clays and bovine serum albumin (BSA) by Fourier Transform Infrared Spectroscopy in order to understand the role of clay morphology on protein conformation. We show that the conformational changes of BSA depend on protein concentration and its initial structure, clay morphology and the clay/protein ratio. The surface curvature radius seems to play a key role in the final conformation. Both the curved nanoscale surface of halloysite nanotubes (HNTs) and the flat morphology of kaolinite (Kao) interfere profoundly on the α/β transitions of BSA. BSA conformation also determines the percentage of protein adsorbed on the clay surface.